Obtenção de emulsões asfálticas modificadas utilizando resíduos industriais - Lima, Cristian Kelly Morais de (2012)
The main objective of this research was the development and characterization of conventional and modified cationic asphalt emulsions. The asphalt emulsions were developed by using the Petroleum Asphalt Cement (CAP 50-70) from Fazenda Belém (Petrobras -Aracati-Ce). The first step in this research was the development of the oil phase (asphalt + solvent) and the aqueous phase (water + emulsifying agent + acid + additives), separately. During the experiments for the obtaining of the conventional asphalt emulsion, the concentration of each constituent was evaluated. For the obtaining of the oil phase, kerosene was used as solvent at 15 and 20 wt.%. For the development of the aqueous phase, the emulsifying agent was used at 0.3 and 3.0 wt.%, whereas the acid and the additive were set at 0.3 wt.%. The percentage of asphalt in the asphalt emulsion was varied in 50, 55, and 60 wt.% and the heating temperature was set at 120 °C. The aqueous phase in the asphalt emulsion was varied from 16.4 to 34.1 wt.% and the heating temperature was set at 60 °C. After the obtaining of the oil and the aqueous phases, they were added at a colloidal mill, remaining under constant stirring and heating during 15 minutes. Each asphalt emulsion was evaluated considering: sieve analysis, Saybolt Furol viscosity, pH determination, settlement and storage stability, residue by evaporation, and penetration of residue. After the characterization of conventional emulsions, it was chosen the one that presented all properties in accordance with Brazilian specifications (DNER-EM 369/97). This emulsion was used for the development of all modified asphalt emulsions. Three polymeric industrial residues were used as modifier agents: one from a clothing button industry (cutouts of clothing buttons) and two from a footwear industry (cutouts of sandals and tennis shoes soles), all industries located at Rio Grande do Norte State (Brazil).The polymeric residues were added into the asphalt emulsion (1 to 6 wt.%) and the same characterization rehearsals were accomplished. After characterization, it were developed the cold-mix asphalts. It was used the Marshall mix design. For cold-mix asphalt using the conventional emulsion, it was used 5, 6 and 7 wt.% asphalt emulsion. The conventional mixtures presented stability values according Brazilian specification (DNER-369/97). For mixtures containing asphalt modified emulsions, it was observed that the best results were obtained with emulsions modified by button residue